Safety and outcome of children, adolescents and young adults participating in phase I/II clinical oncology trials: a 9-year center experience - Pujol Manresa, Anna; Buendía López, Susana; Andión, Maitane; Herrero, Blanca; Lassaletta, Álvaro; Ramirez, Manuel; Ruano, David; Hernández-Marqués, Carmen; Varo, Amalia; de Rojas, Teresa; Cortés Hernández, Marta; Verdú-Amorós, Jaime; et al. (Frontiers in Pediatrics, 2024)
95%CI: 9-15), higher in target-specific versus non-target-specific trials (14 vs 6 months; p=<0.001).Discussion: A significant and increasing number of patients have been included in early clinical trials, suggesting that both oncologists and families consider it valuable to be referred to specialized Units to access new therapies. Moreover, our data suggests that participation in early clinical trials, although not without potential toxicities, might have a positive impact on individual outcomes.